At Crossroads: The Challenges for Geriatric Oncology in India - Sansar, Bipinesh; Gupta, Anuj; Chitre, Ankita; Mishra, Bal Krishna; Lakshmanamurthy, Praveen; Gupta, Pooja; Sahoo, Ajit; Kaur, Navneet; Dey, Somnath; Vinayak, Kunal Ranjan; Kapoor, Akhil (South Asian Journal of Cancer, 2024)
A larger percentage of our population is aging healthily and living on to a ripe old age. 60 years of age is taken as cut-off for identifying geriatric population for the purpose of specialized healthcare. The incidence of cancer is increasing and its expected more so in the geriatric population. At present , there are a limited cancer centres where specialized geriatric clinic is being conducted.Some of the the key unmet needs are — lack of resources and time for dedicated geriatric screening, lack of validated interventions and lack of awareness about the field of geriatric oncology. Some of the proposed solutions are increasing orientation and exposure of trainees and early career oncologists as well as carrying out country specific research to find useful interventions in this field.
Keywords: aging; cancer; geriatric; old; oncology